Efektivitas pengajaran klinik di RSUD dr. H. Abdul Moeloek Provinsi Lampung - Restu Cyntia Permatasari; Merry Indah Sari; Dwita Oktaria; Oktafany (Medula, 2021)
Clinical Clerkships refers to a program designed for medical students to qualify a competent doctor. This program is carried out in the teaching hospital, network hospitals, community health center (Puskesmas) and companies. The aim of the study was to determine the effectiveness of clinical teaching in the RSUD Dr. H. Abdul Moeloek of Lampung Province. This study was a descriptive study using a purposive sampling. The subject of this research were 29 clinical clerkships students in the first data retrieval, and 21 each in the second and third data retrieval in the Department of Surgery at the RSUD Dr. H. Abdul Moeloek of Lampung Province. The data was collected using The Clinical Teaching Effectiveness Instrument (CTEI) and analyzed using univariate analysis.This study showed the overall effectivity of the clinical teaching in RSUD Dr. H. Abdul Moeloek of Lampung Province. Average category was the most frequent accounted for 91.67% while 8.33% cases was in the Good category. The Clinical Teaching Effectiveness in Dr. RSUD H. Abdul Moeloek of Lampung Province was in Average category.